2011
DOI: 10.1063/1.3618721
|View full text |Cite
|
Sign up to set email alerts
|

Dynamical regimes on the Cl + H2 collisions: Inelastic rainbow scattering

Abstract: While Cl + H(2) reactive collisions have been a subject of numerous experimental and theoretical studies, inelastic collisions leading to rotational energy transfer and/or vibrational excitation have been largely ignored. In this work, extensive quantum mechanical calculations covering the 0.5-1.5 eV total energy range and various initial rovibrational states have been carried out and used to perform a joint study of inelastic and reactive Cl + H(2) collisions. Quasiclassical trajectories calculations compleme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 42 publications
1
20
0
Order By: Relevance
“…The semi-quantitative agreement between the classical and quantum P r ( J ) and DCSs seems to indicate that quantum effects associated with interference between the two groups of partial waves are not expected to be important. 41 Therefore, the Cl + H 2 ( v = 0, j = 0) inelastic scattering seems to be a good example of a collision system in which the QCT and QCT GDFs would be similar.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The semi-quantitative agreement between the classical and quantum P r ( J ) and DCSs seems to indicate that quantum effects associated with interference between the two groups of partial waves are not expected to be important. 41 Therefore, the Cl + H 2 ( v = 0, j = 0) inelastic scattering seems to be a good example of a collision system in which the QCT and QCT GDFs would be similar.…”
Section: Resultsmentioning
confidence: 99%
“…Regarding inelastic collisions, some interesting features emerged from previous studies. 41 , 42 QM and QCT calculations using the BW2 PES 43 showed that at relatively high collision energies ( E coll > 0.6 eV) and for small Δ j values (Δ j = j ′ – j ), the inelastic probabilities, P r ( J ), exhibit two maxima separated by a minimum in the QCT and QM results. This minimum was identified as that corresponding to the glory impact parameter.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Aoiz and cowokers have examined the role of long-range attractive forces in l-type rainbow in a series of studies of rotationally inelastic atom + diatomic molecule collisions: Ar+NO, Cl+H 2 , Ne+NO, Xe+NO, and Kr+NO. [31][32][33][34] We note that there is no definitive criterion to classify the rainbows into the two types in advance. 26,28,30 Recent experimental progress in high-resolution measurements of state-to-state DCSs and stereodynamic control of rotationally inelastic collisions may facilitate observation of rainbows with fewer averaging effects.…”
Section: Introductionmentioning
confidence: 99%